La responsabilidad de los árbitros por los incumplimientos de sus obligaciones en el arbitraje - Judkiewicz, Małgorzata (2020)
There is a contractual relation between the parties to a dispute and the arbitrators, which entails the existence of rights and duties on both sides. When arbitrators breach their contractual obligations, their civil liability may be triggered and it is not limited to cases in which the award has been set aside. The civil liability usually arises in cases of gross negligence or wilful misconduct; however, the interpretation of those concepts is not uniform in different jurisdictions.In this article, the author makes a comparative analysis of different sources of the civil liability of arbitrators and presents relevant international case law. In addition, the article explains the arbitrators’ obligations such as the obligation to issue an enforceable award, to be independent and impartial, to ensure equal treatment of the parties and to maintain confidentiality.